Dietary supplementation of Bacillus velezensis improves Vibrio anguillarum clearance in European sea bass by activating essential innate immune mechanisms. Issue 124 (May 2022) - Monzón-Atienza, Luis; Bravo, Jimena; Fernández-Montero, Álvaro; Charlie-Silva, Ives; Montero, Daniel; Ramos-Vivas, José; Galindo-Villegas, Jorge; Acosta, Félix
Abstract: Bacillus spp. supplementation as probiotics in cultured fish diets has a long history of safe and effective use. Specifically, B. velezensis show great promise in fine-tuning the European sea bass disease resistance against the pathogenicity caused by several members of the Vibrio family. However, the immunomodulatory mechanisms behind this response remain poorly understood. Here, to examine the inherent immune variations in sea bass, two equal groups were fed for 30 days with a steady diet, with one treatment supplemented with B. velezensis . The serum bactericidal capacity against live cells of Vibrio anguillarum strain 507 and the nitric oxide and lysozyme lytic activities were assayed. At the cellular level, the phagocytic response of peripheral blood leukocytes against inactivated Candida albicans was determined. Moreover, head-kidney (HK) total leukocytes were isolated from previously in vivo treated fish with LPS of V. anguillarum strain 507. Mechanistically, the expression of some essential proinflammatory genes (interleukin-1 ( il1b ), tumor necrosis factor-alpha ( tnfa ), and cyclooxygenase 2 ( cox2 ) and the sea bass specific antimicrobial peptide (AMP) dicentracin ( dic ) expressions were assessed. Surprisingly, the probiotic supplementation significantly increased all humoral lytic and cellular activities assayed in the treated sea bass. In addition, time-dependent differences were observed between the control and probiotic treated groups for all the HK genes markers subjected to the sublethal LPS dose. Although the il1b was the fastest responding gene to a significant level at 48 h post-injection (hpi), all the other genes followed 72 h in the probiotic supplemented group. Finally, an in vivo bacteria challenge against live V. anguillarum was conducted. The probiotic fed fish observed a significantly higher survival. Overall, our results provide clear vertical evidence on the beneficial immune effects of B. velezensis and unveil some fundamental immune mechanisms behind its application as a probiotic agent in intensively cultured European sea bass. Highlights: B. velezensis strain D-18 as probiotic generates protection in the European sea bass. Innate humoral and cellular mechanisms show significant enhancements in the animals fed with the probiotic. In vivo challenge against a pathogenic strain of Vibrio anguillarum was better resolved by the probiotic fortified fish. The regular use of B. velezensis is suggested as a viable eco-friendly strategy to prevent bacterial diseases in fish culture.